Long-term oral administration of Huaier granules improves survival outcomes in hepatocellular carcinoma patients within Milan criteria following microwave ablation: a propensity score matching and stabilized inverse probability weighting analysis - Xie, Kailing; Ma, Mingxiu; Xu, Feng (Frontiers in Pharmacology, 2024)
Objective: This study aimed to elucidate the therapeutic effects of Huaier granules on hepatocellular carcinoma (HCC) within the Milan criteria in patients who underwent microwave ablation (MWA). Materials and Methods: A total of 228 patients were included, with 97 in the Huaier group and 131 in the control group. We evaluated progression-free survival (PFS), overall survival (OS), and extrahepatic metastasis survival (EMS) using Kaplan–Meier (KM) curves with a log-rank test. Propensity Score Matching (PSM) and Stabilized Inverse Probability of Treatment Weighting (IPTW) were performed to minimize selection and confounding biases. Results: Following PSM, the 1-, 3-, and 5-year PFS rates in the Huaier and control groups were 83.5% vs. 70.7%, 57.7% vs. 42.6%, and 43.6% vs. 31.9% (p = 0.030), respectively. The 1-, 3-, and 5-year OS rates were 98.9% vs. 95.6%, 83.9% vs. 72.3%, and 72.2% vs. 53.7% (p = 0.023), respectively. The corresponding 1-, 3-, and 5-year EMS rates were 98.9% vs. 93.4%, 91.7% vs. 83.7%, and 91.7% vs. 78.5% (p = 0.039), respectively. Stabilized IPTW analysis of KM curves yielded results similar to those of the PSM analysis. Additionally, administering Huaier granules for at least 6 months significantly improved PFS and OS. Conclusions: Huaier granules can reduce the risk of recurrence and improve the OS of patients with HCC within the Milan criteria following MWA. Administering Huaier granules for over 6 months proved beneficial.